-5x-8=13+8(x+3)

Simple and best practice solution for -5x-8=13+8(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-8=13+8(x+3) equation:


Simplifying
-5x + -8 = 13 + 8(x + 3)

Reorder the terms:
-8 + -5x = 13 + 8(x + 3)

Reorder the terms:
-8 + -5x = 13 + 8(3 + x)
-8 + -5x = 13 + (3 * 8 + x * 8)
-8 + -5x = 13 + (24 + 8x)

Combine like terms: 13 + 24 = 37
-8 + -5x = 37 + 8x

Solving
-8 + -5x = 37 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-8 + -5x + -8x = 37 + 8x + -8x

Combine like terms: -5x + -8x = -13x
-8 + -13x = 37 + 8x + -8x

Combine like terms: 8x + -8x = 0
-8 + -13x = 37 + 0
-8 + -13x = 37

Add '8' to each side of the equation.
-8 + 8 + -13x = 37 + 8

Combine like terms: -8 + 8 = 0
0 + -13x = 37 + 8
-13x = 37 + 8

Combine like terms: 37 + 8 = 45
-13x = 45

Divide each side by '-13'.
x = -3.461538462

Simplifying
x = -3.461538462

See similar equations:

| 7x+8+8x+3=17x-19 | | 3.8-(7.45)= | | 67m-27m-18m-21m+8=81 | | 10x+15y=200 | | 0=(-5/7)x+4 | | 5x-2=-52 | | 3x-12y-4xy+x^2=0 | | 41s-11s-29s=26 | | .99n+98=1.98n | | 7-7x=-77 | | 9m-3=2m+46 | | 7w-12w+24=11 | | X-10=-6+2x | | 2d+19d+13d-32d=26 | | 6x-36=7 | | 6x-4=-76 | | -6x^2+9x+3=0 | | 8y-10=6y | | 5(2x-3)-x=x+1 | | 52u+9u+12u+4u-72u=75 | | 2x+8x=23.2 | | 1.07=2.3-1.2x | | -2+2x=20 | | 3n-8=2 | | x+2+8+x=20 | | 9x+2y=20 | | 61a-62a-31=-11 | | 2x+3=-1+3x | | 10x-6x-3x=2 | | -2x+3-4-4x=-10x+3+5x | | [3(7-5)-6]-[7-(2-6)]= | | 25y=15y^2 |

Equations solver categories